Cellular Localization and Biochemical Characterization of a Chimeric Fluorescent Protein Fusion of Arabidopsis Cellulose Synthase-Like A2 Inserted into Golgi Membrane. (14th January 2014) - De Caroli, Monica; Lenucci, Marcello S.; Di Sansebastiano, Gian-Pietro; Tunno, Michela; Montefusco, Anna; Dalessandro, Giuseppe; Piro, Gabriella
Abstract : Cellulose synthase - like ( Csl ) genes are believed to encode enzymes for the synthesis of cell wall matrix polysaccharides. The subfamily of CslA is putatively involved in the biosynthesis of β -mannans. Here we report a study on the cellular localization and the enzyme activity of an Arabidopsis CslA family member, AtCslA2. We show that the fluorescent protein fusion AtCslA2-GFP, transiently expressed in tobacco leaf protoplasts, is synthesized in the ER and it accumulates in the Golgi stacks. The chimera is inserted in the Golgi membrane and is functional since membrane preparations obtained by transformed protoplasts carry out the in vitro synthesis of a 14 C-mannan starting from GDP-d -[U- 14 C]mannose as substrate. The enzyme specific activity is increased by approximately 38% in the transformed protoplasts with respect to wild-type. Preliminary tests with proteinase K, biochemical data, and TM domain predictions suggest that the catalytic site of AtCslA2 faces the Golgi lumen.